Data Analysis by Web Scrapping: An Application Python - M. Revati, Ch. Raja Jacob, K. Ashok, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The standard information investigation is built on the root and impact relationship, shaped an example minuscule examination, subjective and quantitative examination, the rationality approach of creating extrapolation examination. The Web Scraper's conniving ethics and procedures are juxtaposed, it explains about the working of how the scraper is premeditated. The technique of it is allocated into three fragments: the web scraper draws the desired links from web, and then the data is extracted to get the data from the source links and finally stowing that data into a csv file. The Python language is implemented for the carrying out. By doing so, linking all these with the moral knowledge of libraries and working know-how, we can have an adequate Scraper in our hand to produce the desired result. Due to an enormous community and library resources for Python and the exquisiteness of coding chic of python language, it is most appropriate one for Scraping desired data from the desired website